ELECTRICAL CONDUCTIVITY IN THE QUANTUM-SIZE EFFECTS OF COMPOSITE MATERIALS CONTAINING NANOPARTICLES OF METALS - Boymuratov Fakhriddin Тog’aymuradovich; Abdurakhmanov Umarbek; Isayev Xamid; Urazaliyev Roziqjon Turanovich (Galaxy International Interdisciplinary Research Journal, 2021)
The interest in nanoobjects can be explained by the fact that reducing materials to nanometer sizes leads to the manifestation of so-called “quantum-size effects” in them, when the sizes of the objects under study are comparable to the de Broglie wavelength of electrons, phonons and excitons. It is found that the percolation-like behaviour of σ and ε, which is observed when the Ni particles are the sizes of 1-3 µm (micro-dispersed particles), gave way to another behaviour characterized by an additional contribution to σ and ε below the percolation threshold when the Ni particles are the sizes of ≤ 30 nm (nanoparticles). This peculiarity of the behaviour of σ and ε of the composites can be explained in the frame of the network hierarchy model of composites, which was proposed recently by Balberg et al.